Monitoring protein dynamics in protein O-mannosyltransferase mutants in vivo by tandem fluorescent protein timers - Castells Ballester, Joan; Zatorska, Ewa; Meurer, Matthias; Neubert, Patrick; Metschies, Anke; Knop, Michael; Strahl, Sabine (Molecules, 2018)
For proteins entering the secretory pathway, a major factor contributing to maturation and homeostasis is glycosylation. One relevant type of protein glycosylation is O-mannosylation, which is essential and evolutionarily-conserved in fungi, animals, and humans. Our recent proteome-wide study in the eukaryotic model organism Saccharomyces cerevisiae revealed that more than 26% of all proteins entering the secretory pathway receive O-mannosyl glycans. In a first attempt to understand the impact of O-mannosylation on these proteins, we took advantage of a tandem fluorescent timer (tFT) reporter to monitor different aspects of protein dynamics. We analyzed tFT-reporter fusions of 137 unique O-mannosylated proteins, mainly of the secretory pathway and the plasma membrane, in mutants lacking the major protein O-mannosyltransferases Pmt1, Pmt2, or Pmt4. In these three pmtΔ mutants, a total of 39 individual proteins were clearly affected, and Pmt-specific substrate proteins could be identified. We observed that O-mannosylation may cause both enhanced and diminished protein abundance and/or stability when compromised, and verified our findings on the examples of Axl2-tFT and Kre6-tFT fusion proteins. The identified target proteins are a valuable resource towards unraveling the multiple functions of O-mannosylation at the molecular level.
Gesehen am 02.04.2019